2005
DOI: 10.1179/174329305x37051
|View full text |Cite
|
Sign up to set email alerts
|

Fluxless laser beam joining of aluminium with zinc coated steel

Abstract: A laser welding-brazing (LWB) process to join zinc coated steel and aluminium sheets in two different flange geometries is reported. The deep drawing steel sheets are covered by a zinc layer of maximum thickness 10 mm, and a zinc based filler wire was used in the welding experiments with a Nd-YAG laser. Because of the differences in melting temperatures between iron (1808 K), aluminium (933 K), and zinc (693 K), it is possible to weld the aluminium alloy only. Owing to the zinc coating on the steel side, a Zn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 14 publications
0
42
1
Order By: Relevance
“…Another interesting direction is the laser welding of dissimilar materials, i.e., Fe and Al alloys, which is important for the aerospace and automobile industries where serious difficulties are caused by the high brittleness of the intermetallide phases generated in the melting pool [26][27][28][29][30][31]. On knowing the succession of the phase-structural transformations in the laser weld joint, it is possible to attain the fabrication creation of such a barrier layer of the alloying elements [26,27,30], that is capable of wetting the joining alloys on the basis of iron and aluminum, which protects them from the contact during the melting and prevents the formation of undesirable phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting direction is the laser welding of dissimilar materials, i.e., Fe and Al alloys, which is important for the aerospace and automobile industries where serious difficulties are caused by the high brittleness of the intermetallide phases generated in the melting pool [26][27][28][29][30][31]. On knowing the succession of the phase-structural transformations in the laser weld joint, it is possible to attain the fabrication creation of such a barrier layer of the alloying elements [26,27,30], that is capable of wetting the joining alloys on the basis of iron and aluminum, which protects them from the contact during the melting and prevents the formation of undesirable phases.…”
Section: Introductionmentioning
confidence: 99%
“…On knowing the succession of the phase-structural transformations in the laser weld joint, it is possible to attain the fabrication creation of such a barrier layer of the alloying elements [26,27,30], that is capable of wetting the joining alloys on the basis of iron and aluminum, which protects them from the contact during the melting and prevents the formation of undesirable phases. Different methods of the plasticity improvement of such welded joints exist, such as crystallographic structure modification, boundary strengthening, grain size decrease, columnar structure creation, micro-and macro-alloying.…”
Section: Introductionmentioning
confidence: 99%
“…15,16) The solid state welding techniques are expected to restrain the growth of the intermetallic compound layer within a permissible limit, which has been identified as 10 μm thickness, 17) but the adaptability of these methods is restricted in automotive industry due to equipment configuration. In the last few years, arc welding-brazing, [18][19][20][21] laser reactive wetting 6) and laser brazing 4,5,[22][23][24][25] of the dissimilar materials of steel and aluminum alloy have drawn great attentions. Lin et al [18][19][20] studied dissimilar metals TIG welding-brazing of aluminum alloy to stainless steel using Al-Si, Al-Cu and Al-Si-Cu filler wires.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptability of these solid state welding methods is restrained to a certain extent in automotive industry due to the limitation on configuration and capacity of welding equipments. Besides, arc welding-brazing [19,20] and laser brazing [21][22][23] are also employed to weld aluminium alloy and steel. The results indicated that composition, morphology and thickness of the intermetallic compounds could be regulated with the introduction of filler metals, whereas cracks also tended to initiate at the intermetallic compounds and then propagate through them.…”
Section: Introductionmentioning
confidence: 99%